2023
DOI: 10.1093/hr/uhad162
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor CsS40 negatively regulates TCS1 expression and caffeine biosynthesis in connection to leaf senescence in Camellia sinensis

Xinzhuan Yao,
Hufang Chen,
Antao Ai
et al.

Abstract: Caffeine is considered as one of the most important bioactive components in the popular plant beverages tea, cacao, and coffee, but as a wide-spread plant secondary metabolite its biosynthetic regulation at transcription level remains largely unclear. Here, we report a novel transcription factor Camellia sinensis Senescnece 40 (CsS40) as a caffeine biosynthesis regulator, which was discovered during screening a yeast expression library constructed from tea leaf cDNAs for activation of tea caffeine synthase (TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…19,21 In addition, a novel senescenceassociated transcription factor, CsS40, was found to regulate caffeine biosynthesis by downregulating the biosynthetic gene TCS1. 20 However, there is limited understanding regarding the regulatory mechanisms of theobromine biosynthesis. It has been reported that CsMYB184 (TEA029017.1) seemed to be involved in the biosynthesis of theobromine, but this needs to be further verified.…”
Section: ■ Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…19,21 In addition, a novel senescenceassociated transcription factor, CsS40, was found to regulate caffeine biosynthesis by downregulating the biosynthetic gene TCS1. 20 However, there is limited understanding regarding the regulatory mechanisms of theobromine biosynthesis. It has been reported that CsMYB184 (TEA029017.1) seemed to be involved in the biosynthesis of theobromine, but this needs to be further verified.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Theobromine has received more and more attention as an important alkaloid in tea plant. Up to this point, only CsNAC7 and CsMYB184 have been functionally identified as regulators of caffeine biosynthesis, with each one specifically enhancing the expression of the critical biosynthetic genes NMT1 and TCS1 , respectively. , In addition, a novel senescence-associated transcription factor, CsS40, was found to regulate caffeine biosynthesis by downregulating the biosynthetic gene TCS1 . However, there is limited understanding regarding the regulatory mechanisms of theobromine biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the method of Yao et al, each leaf tissue culture seedling was cut into four parts and infected inside a resuspension (containing 100 μmol/L AS) containing no-load, 35S: CsHIPP3 , 35S: CsF3′5′H1 , and co-overexpression bacterial solution for 20 min. The leaves were grown on MS solid medium supplemented with 1.0 mg/L NAA and 0.5 mg/L 6-BA for 3 days in the dark after being dried using sterile absorbent paper.…”
Section: Methodsmentioning
confidence: 99%